Comparison of Modal Parameters of a Square Steel Plate Using Finite Element Method and Operational Modal Analysis - Azhar, Anis Shafiqah; Abdul Kudus, Sakhiah; Jamadin, Adiza; Mustaffa, Nur Kamaliah (International Journal of Integrated Engineering, 2023)
In engineering domains, modal analysis is a field that is studied extensively with the goal of better characterising components or structures. The modal analysis produces modal parameters, which are essential properties of a system that can be employed for damage identification, vibration analysis, and structural health monitoring. Plated element’s relevance in various applications makes it an intriguing vibration study subject. In this research, modal analysis was performed on a square steel plate in free ends condition. This work aimed to provide a complete anatomical description of this complex boundary condition and its implications on modal parameters. Before comparing modal parameters with experimental data, a primary modal analysis was performed using finite element (FE) method. Then experimental analysis was conducted under the operational modal analysis setup (OMA).  As the results, six natural frequencies are retrieved and compared amongst the two methods, recording the maximum of 6% percentage difference from the readings. This implied a close values estimated between the methods used. For mode shapes, nine modes are identified from FE method and discussed according to established free plate vibration studies, while three similarly identified modes successfully recognized by using OMA.